CAMELLIA QUYNHII (THEACEAE, SECT. STEREOCARPUS), A NEW YELLOW SPECIES FROM THE CENTRAL HIGHLANDS, VIETNAM - Quach, Van Hoi (Trường Đại học Đà Lạt, 2023)
Camellia quynhii is described and illustrated as a new species of section Stereocarpus (Pierre) Sealy from 12th village, Vu Bon Commune, Krong Pak District, Dak Lak Province. C. quynhii resembles C. dormoyana (Pierre) Sealy but differs in several morphological characteristics: sepals 6–7; petals about 12–15; filaments tomentose at the base; style 3(–4), basally united; capsule 3(–4) locular, 2–6 seeds in each locule. Information on its phenology, distribution, ecology, and conservation status is also provided.